2018
DOI: 10.1016/j.pedneo.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal cord at delivery and perinatal outcomes: Single-center retrospective study, with emphasis on fetal acid-base balance

Abstract: Perinatal outcomes of pregnancies with nuchal cord in predominantly African American and Hispanic women were not adversely affected. Analysis of umbilical cord blood gases suggests mixed respiratory and metabolic fetal acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 17 publications
5
26
0
Order By: Relevance
“…No significant relationship between nuchal cord and birth weight <2500g (OR 0.66; 95% CI 0.50, 1.35), or fetal growth restriction or small for gestational age infants (OR 1.41; 95% CI 0.90, 2.21) was identified. Studies of fetal growth restriction and small for gestational age were combined as they used a wide range of definitions [8,[38][39][40][41][42][43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…No significant relationship between nuchal cord and birth weight <2500g (OR 0.66; 95% CI 0.50, 1.35), or fetal growth restriction or small for gestational age infants (OR 1.41; 95% CI 0.90, 2.21) was identified. Studies of fetal growth restriction and small for gestational age were combined as they used a wide range of definitions [8,[38][39][40][41][42][43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…36% of overall cases being a primi. However, a strong association with advanced maternal age cannot be commented because of various socio-cultural factors, even though in a study by Vasa R et al [11] strong pre-disposition was seen in age 20-34 years, however author denied any relevance with maternal age due to longitudinal socio-cultural factors. Since in our study all patients were racially homogenous, we cannot comment on its association with CAN, but in multiple studies no racial relevance was identified.…”
Section: Discussionmentioning
confidence: 94%
“…Since in our study all patients were racially homogenous, we cannot comment on its association with CAN, but in multiple studies no racial relevance was identified. [11] As far as maternal morbidity is concerned no major life-threatening events were noted as an effect of nuchal cords ante-natally except co-existing medical conditions which seemingly has no role in CAN causation, neither its evidenced by other authors. About 7% patients had some obstetrical issue, mainly breech presentation, PROM and cord-prolapse, for which no relevant evidence can be found in contemporary studies and should be further investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Thus effect of nuchal cord on fetus is suggested to be only transient without long term effect. Meconium stained liquor was seen in 9% of deliveries but only 2.3% of newborns suffered from meconium aspiration syndrome ( 8,12,19,20 The neonatal complications which were observed were not serious but were treatable and mostly occurred with tight nuchal cord but were not statistically significant.…”
Section: Neonatal Outcomementioning
confidence: 98%